Dasatinib in the Management of Pediatric Patients With Philadelphia Chromosome-Positive Acute Lymphoblastic Leukemia - Cerchione, Claudio; Locatelli, Franco; Martinelli, Giovanni (Frontiers in Oncology, 2021)
Acute leukemia is the most common cancer in childhood; in particular, acute lymphoblastic leukemia (ALL) represents roughly up to 80% of all cases of acute leukemias in children. Survival of children with ALL has dramatically improved over the last few decades, and is now over 90% (versus 40% of adult patients) in developed countries, except for in infants (i.e., children < 1 year), where no significant improvement was registered. Philadelphia positive ALL (Ph+ALL) accounts for around 3% of cases of childhood ALL, its incidence increasing with patient’s age. Before the era of tyrosine-kinase inhibitors (TKIs), pediatric Ph+ALL showed a worse prognosis in comparison to other forms of ALL, and was managed with intensive chemotherapy, followed, whenever possible, by allogenic hematopoietic stem cell transplantation (HSCT) in first morphological complete remission. TKIs have revolutionized the current clinical approach, which involves combinations of imatinib plus standard chemotherapy that can abrogate the negative prognostic impact conferred by the presence of BCR/ABL1 rearrangement, resulting in the probability of event-free survival (EFS) being significantly better than that recorded in the pre-TKI era. Long-term follow-up confirms these data, questioning the role of a real advantage offered by HSCT over intensive chemotherapy plus TKI in all Ph+ALL pediatric patients. Imatinib was the first generation TKI and the prototype of targeted therapy, but over the years second- (dasatinib, nilotinib, bosutinib) and third-generation (ponatinib) TKIs showed a capacity to overcome resistance to imatinib in Ph+ hematological neoplasms. Given the effectiveness of the first-in-class TKI, imatinib, also the second-generation TKI dasatinib was incorporated in the treatment regimens of Ph+ALL. In this manuscript, we will discuss the role of this drug in pediatric Ph+ALL, analyzing the available data published to date.